1993
DOI: 10.1159/000107293
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tetrahydroaminoacridine Treatment of Alzheimer's Disease Evaluated Clinically and by Regional Cerebral Blood Flow and EEG

Abstract: Neurochemical evidence indicates that cognitive impairment in dementia of Alzheimer type (DAT) is related to degeneration of cholinergic neurons in the brain. A pharmacological approach is treatment with a cholinesterase inhibitor such as tetrahydroaminoacridine (THA). THA treatment of 17 patients with DAT was studied with a double-blind crossover design with three types of treatment, THA + lecithin, THA + placebo and placebo + placebo. Each treatment period was 6 weeks with wash out periods of 2 weeks. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 12 publications
3
49
0
Order By: Relevance
“…The reduction of delta power under rivastigmine observed in this study is in line with the EEG changes reported under treatment with the older cholinesterase inhibitors physostigmine [24,26] and tetrahydroaminacridine [27,28]. This finding may be attributed to an enhancement of cholinergic neurotransmission under rivastigmine treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reduction of delta power under rivastigmine observed in this study is in line with the EEG changes reported under treatment with the older cholinesterase inhibitors physostigmine [24,26] and tetrahydroaminacridine [27,28]. This finding may be attributed to an enhancement of cholinergic neurotransmission under rivastigmine treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Pharmacological studies in healthy individuals showed an increase in absolute EEG delta power after the application of the muscarinic acetylcholine antagonist scopolamine [23]. On the other hand, EEG slow-wave power in Alzheimer patients decreased subsequent to the administration of the acetylcholinesterase-inhibiting drugs physostigmine and tetrahydroaminoacridine (tacrine) [24][25][26][27][28]. Corresponding data for the newer acetylcholinesterase inhibi- Thus, we studied the effects of rivastigmine, an acetylcholinesterase inhibitor with established therapeutic efficacy in Alzheimer's disease [29], on the EEG power spectrum in a group of Alzheimer patients.…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in classical qEEG parameters was reported after short-term [11], medium-term (e.g., 6 weeks) [12], and even long-term [13] therapy. Very recently, a power reduction in slow frequencies has been observed after 5 days of rivastigmine therapy as well [14].…”
Section: Introductionmentioning
confidence: 93%
“…An improvement in EEG activity with an increase in mean frequency and a decrease in slow frequency [7][8][9][10] have been observed following long-term treatment with tacrine in AD patients. Similarly, increases in brain glucose metabolism [11][12][13] as well as cerebral blood flow [14] have been measured by positron emission tomography (PET) following tacrine treatment. Long-term treatment with tacrine for some years has shown some significant effect on tests of primary memory, episodic memory, visuospatial ability and psychomotor speed, when doses were adjusted repeatedly [15,16].…”
Section: Introductionmentioning
confidence: 99%